METHODS FOR ASSESSING STUDENTS' SPATIAL THINKING THROUGH DESCRIPTIVE GEOMETRY TASKS - Yuldashev Solmonjon Iqboljon ugli (Modern American Journals, 2025)
This article explores the scientific and methodological foundations for assessing and developing students' spatial thinking through descriptive geometry tasks. The study analyzes the compatibility of graphic assignments with spatial cognition components, assessment criteria, cognitive indicators, and diagnostic approaches using modern technologies. Based on experimental results, the dynamics of students’ spatial reasoning improvement were identified, and the effectiveness of using geometric tasks to develop spatial thinking was substantiated. Practical recommendations for improving assessment systems for instructors are also provided.
Keywords: Descriptive geometry, spatial thinking, graphic tasks, assessment methodology, visual logic, spatial diagnostics.